Factor XIIIA—expressing inflammatory monocytes promote lung squamous cancer through fibrin cross-linking - Alessandro Porrello (Nature Portfolio, 2018)
Lung squamous carcinomas (LUSC) are poorly molecularly characterized, but sub-populations show promising response to immune checkpoint inhibitors. Here, the authors identify a subset of LUSC characterized by infiltration of inflammatory monocytes, where metastasis is linked to Factor XIIIA promoting fibrin cross-linking.